Perioperative management strategy of severe traumatic brain injury during the outbreak of COVID-19 - Peng Chen; Xue-Hua Xiong; Ying Chen; Ke Wang; Qing-Tao Zhang; Wei Zhou; Yong-Bing Deng (Chinese Journal of Traumatology, 2020)
Since December 2019, a pneumonia caused by a new coronavirus, i.e. COVID-19 occurred in Wuhan, Hubei Province, China. Although the epidemic in China has been bought under control, the global COVID-19 situation is still grim. Severe traumatic brain injury (TBI), as one of critical conditions in the department of neurosurgery, requires an early and effective treatment, especially surgery. There were currently no reliable guidelines on how to perform perioperative protection in TBI patients with suspected or confirmed coronavirus infection. According to the corresponding treatment regulations and guidelines issued by the authorities, we summarized the management strategy of TBI patients in perioperative period during the COVID-19 outbreak based on medical and nursing practice, in order to provide a reference for clinicians.